Medical care and payment for diabetes in China: enormous threat and great opportunity. - Wenying Yang (Public Library of Science (PLoS), 2012)
Background The Diabetes Impact Study followed up a large national population-based screening study to estimate the use of and expenditures for medical care caused by diabetes in China and to ascertain the use and cost of essential basic medicines and care. Methods In 2009-10, the study team interviewed 1482 adults with diabetes and 1553 adults with glucose tolerance in the normal range from population-based random samples at 12 sites in China. The response rate was 67%. Findings After adjusting for age, sex, and urban/rural location, people with diabetes received 1.93 times more days of inpatient treatment, 2.40 times more outpatient visits, and 3.35 times more medications than people with normal glucose tolerance (all p<0.05). Adjusted expenditures for medical care were 3.38 times higher among people with diabetes than among people with normal glucose tolerance (p<0.01, unadjusted 3.97). Persons who were diagnosed with ≥ 10 years prior to the survey paid 3.75 times as much for medical care as those with ≤ 5 years of diagnosed diabetes. Among persons with diabetes, 45.2% took medication to control blood sugar, 21.1% took an antihypertensive medicine, 22.4% took daily aspirin, and 1.8% took a statin. Over the three months before the interview, 46.1% of persons with diabetes recalled seeing a doctor, 48.9% recalled a blood pressure measurement, and 54.5% recalled a blood sugar test. Over the year preceding the interview, 32.1% recalled a retinal screening and 17.9% recalled a foot examination. Conclusions In China, health care use and costs were dramatically higher for people with diabetes than for people with normal glucose tolerance and, in relative terms, much higher than in industrialized countries. Low-cost generic medicines that would reduce diabetes expenditures were not fully used.